“We are outside, not inside”: Refugee women’s life stories of transition through language and literacy - Kajee, Leila (JALL (Journal of Applied Linguistics and Literacy), 2025)
Globally, nearly 120 million people are displaced, placing immense pressure on countries like South Africa to integrate refugees. Although the South African Constitution grants refugees’ rights similar to citizens—excluding voting and holding office—many still face severe challenges. These include integration struggles, language barriers, xenophobia, sexual abuse, and isolation. Feminist scholarship emphasizes the gendered nature of displacement, with women often assuming new roles as primary caregivers and breadwinners. This paper explores how refugee women navigate social spaces in host communities through language and literacy practices, challenging negative stereotypes that portray them as either victims or threats. An interpretative study involving 35 women, with four detailed narratives, reveals the complexities of their experiences. By examining their life stories, the study uncovers their resilience and agency. These insights offer valuable understanding of how refugee women adapt, build lives, and become active participants in their new communities despite facing significant obstacles.